Analysis on Carbon Reduction Effect of Vegetation System in Northern China. (August 2015) - Shao, Weiwei; Zhang, Haixing; Yang, Guiyu; Liu, Jiahong; Huang, Hao
Abstract: The present study preliminarily estimated carbon sink of forest and carbon sink of grassland of 13 provinces of the northern China, analyzed their spatial pattern characteristics and revealed the effect of carbon reduction of the northern vegetation system in China using the forest carbon sink volume method and grassland carbon sequestration rate method by using the forest resources inventory data in China and the relevant statistical data. Analysis results illustrated that the total volume of forest carbon sink of the northern China was about 1.2*10 8 t, of which the advantages of the forest carbon sink of Heilongjiang, Inner Mongolia, Shaanxi and Jilin were significant. The total volume of carbon sink of grassland was about 1.78*10 8 t, of which the advantages of the forest carbon sink of Inner Mongolia, Xinjiang, Heilongjiang and Shanxi were significant. It was suggested in this paper that the north China should transform mode of development to further strengthen afforesting and forestation work. The Northeast China should further dig potential of carbon sink of forest and participate in the international carbon trading. The development in the northwest area of China should further strengthen the construction of ecological environment to keep capacity of carbon sink.